2007
DOI: 10.1007/s10545-007-0483-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response to persistent, low‐level β‐glucuronidase expression in the murine model of mucopolysaccharidosis type VII

Abstract: Mucopolysaccharidosis type VII (MPS VII) is a lysosomal storage disease caused by beta-glucuronidase (GUSB) deficiency. This disease exhibits a broad spectrum of clinical signs including skeletal dysplasia, retinal degeneration, cognitive deficits and hearing impairment. Sustained, high-level expression of GUSB significantly improves the clinical course of the disease in the murine model of MPS VII. Low levels of enzyme expression (1-5% of normal) can significantly reduce the biochemical and histopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…3A). Such enzyme levels might normally be sufficient to correct the disease phenotype in lysosomal storage diseases (41,42). However, it may be that a higher The levels of various cytokines were measured in brain homogenates from treated and untreated WT and Ppt1 −/− animals.…”
Section: Discussionmentioning
confidence: 99%
“…3A). Such enzyme levels might normally be sufficient to correct the disease phenotype in lysosomal storage diseases (41,42). However, it may be that a higher The levels of various cytokines were measured in brain homogenates from treated and untreated WT and Ppt1 −/− animals.…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be a very low threshold of activity in LSDs above which lysosomal enzymes are capable of coping with substrate influx and avoiding accumulation. Preclinical studies of ERT or gene therapy approaches in other forms of MPS have demonstrated that low levels of circulating enzyme (as low as 5% of normal) can mediate the correction of GAG accumulation in most somatic tissues (54,55). This low enzymatic activity requirement for disease correction is further supported by clinical evidence; a clear correlation between MPS IIIA clinical manifestations and the patients' underlying mutations have recently been demonstrated in a large cohort of MPS IIIA-affected individuals (2).…”
Section: Figurementioning
confidence: 93%
“…Nevertheless, the circulating GUSB activity after 60 days (below 5% of normal activity) could be unsufficient to achieve substantial clinical improvement in this work, as it has been shown earlier with 2.5% of circulating GUSB activity. 11 More specially, higher enzyme restoration may be required to completely reverse some pathological changes, such as brain or articular abormalities, as we observed poor improvements of morphological abnormalities after plasmid injection.…”
Section: Plasmid-mediated Gene Therapy In Mps VII Mouse Model M Richamentioning
confidence: 82%
“…5 Second, it is also known that 1-5% only of the normal level of GUSB activity are sufficient to reduce biochemical and histopathological abnormalities of the MPS VII disease in some organs. [6][7][8][9][10][11] Therefore, the gene transfer localized to a depot organ such as the liver or the muscle could enable the secretion of the affected enzyme into circulation at a therapeutic level, leading to the global correction of lysosomal storage. Gene therapy of MPS has been pursued primarily using viral vectors.…”
Section: Introductionmentioning
confidence: 99%